The roles of Islamic finance educators in promoting education for sustainable development. - Mohamad Ali, Afiza (2019)
Education is UNESCO’s top priority because it is a basic human right and the foundation that build peace and drive sustainable development. This effort made by UNESCO since 1992 and the new 2030 Agenda for Sustainable Development reflects the important of education system to define their relevant learning objectives and learning outcomes. This is reflected as one of the Sustainable Development Goals which explicitly focus on education which is Sustainable Development Goal 4. Moreover, International Islamic University Malaysia (IIUM) which is now 35 years old since 1983, was founded upon Islamic principles should promote quality education for mankind and produce balanced graduates. IIUM is unique in a way that the objective of the University has been to redefine the concept of education practiced in a liberal and secular environment by integrating Islamic revealed knowledge and human sciences. Hence, it aspires to produce better quality intellects by integrating the qualities of faith, knowledge and good character. The objective of this paper is to present the university educators vision in promoting education for sustainable development. This paper discusses the opinion of Islamic finance educators in implementing the proposed framework on the competences for educators in education for sustainable development namely: (i) learning to know; (ii) learning to do; (iii) learning to live together; and (iv) learning to be, in the context of both conventional and Islamic perspective. Also, the issues in developing education for sustainable development for Islamic finance education are highlighted. The paper adopts qualitative method by interviewing Islamic finance educators in IIUM Institute of Islamic Banking and Finance to understand the issues and discuss the opinion on the sustainable education framework on competences. It is expected that the findings of this study will contribute to the policy makers in supporting Sustainable Development Goal 4.